2019 21st International Conference on Transparent Optical Networks (ICTON) 2019
DOI: 10.1109/icton.2019.8840552
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Combined Effect of Laser Phase Noise and Intercore Crosstalk on the Outage Probability of DD OOK Systems

Abstract: We study the influence of the combined effect of laser phase noise and intercore crosstalk on the outage probability of direct-detection 10 Gbit/s on-off keying optical communication systems. We show that the laser phase noise can affect significantly the outage probability, for lasers with linewidths in the MHz range, for low and high skew-bit rate products. We also show that the laser phase noise effect on the received eye-pattern is qualitatively similar to the one found for high skew-bit rate product in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The number of PMPs is chosen to be high enough to characterize the ICXT mechanism rigorously (Cartaxo et al, 2016). Two different skews, |S mn •R s |=1000 and |S mn •R s |=0.01, are also chosen according to the conditions i) |S mn •R s |≫1, where the symbol rate of the PAM signal is much higher than the ICXT decorrelation bandwidth (which is proportional to the inverse of the skew) and the ICXT creates amplitude levels that seem to exhibit a "noise" like-behavior (Rebola et al, 2019b), and ii) |S mn •R s |≪1, where the symbol rate of the PAM signal is much lower than the ICXT decorrelation bandwidth and well-defined amplitude levels in the eye-patterns are created due to ICXT (Rebola et al, 2019a), . Although intra-datacenters operate at a typical 1310 nm wavelength, the wavelength may need to be extended to 1550 nm to increase the transmission capacity.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The number of PMPs is chosen to be high enough to characterize the ICXT mechanism rigorously (Cartaxo et al, 2016). Two different skews, |S mn •R s |=1000 and |S mn •R s |=0.01, are also chosen according to the conditions i) |S mn •R s |≫1, where the symbol rate of the PAM signal is much higher than the ICXT decorrelation bandwidth (which is proportional to the inverse of the skew) and the ICXT creates amplitude levels that seem to exhibit a "noise" like-behavior (Rebola et al, 2019b), and ii) |S mn •R s |≪1, where the symbol rate of the PAM signal is much lower than the ICXT decorrelation bandwidth and well-defined amplitude levels in the eye-patterns are created due to ICXT (Rebola et al, 2019a), . Although intra-datacenters operate at a typical 1310 nm wavelength, the wavelength may need to be extended to 1550 nm to increase the transmission capacity.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The high number of PMPs is chosen to characterize the ICXT statistics rigorously [11]. Two different skew-symbol rate products (SSRPs) are analyzed: (i) |S mn • R s | 1, where the symbol rate of the PAM4 signal is much higher than the ICXT decorrelation bandwidth [14], and the ICXT creates amplitude levels in the received eye-pattern that seem to exhibit a "noise"-like behavior [21], and (ii) |S mn • R s | 1, where the symbol rate of the PAM4 signal is much lower than the ICXT decorrelation bandwidth [14] and well-defined amplitude levels in the eye-patterns are created due to ICXT [21]. Throughout this section, the OP dependence of the inter-DCI PAM4 link with MCF supported transmission on the MCF length, SSRP, ICXT level, and number of interfering cores is studied.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The ICXT impact on the OOK system performance has been assessed by comparing experimental and simulated BERs and OPs in weakly-coupled MCFs [19] and by comparison with theoretical results [20]. The dependence of the OP due to ICXT on several parameters and features of OOK systems, such as the laser linewidth [21], skew-symbol rate product [21,22], and ICXT level [19,22] has been studied. The impact of ICXT on the performance of PAM4 IM-DD systems has also been assessed [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In signals containing a strong optical carrier, like on-off keying (OOK), a high level of ICXT fluctuations occurs even for large skew and symbol rates [7]. Preliminary simulation results have also shown that the combined effect of the ICXT and laser phase noise can significantly affect the received eye-pattern and outage probability of 10 Gb/s OOK WC-MCF systems [8]. In this work, the impact of the laser phase noise on the instantaneous ICXT power, on the STAXT power and on the performance of DD-OOK WC-MCF systems is investigated.…”
Section: Introductionmentioning
confidence: 99%